Vargas and the roots of the development project in Brazil - Garcia, Francisco Tadeu Lima (Laboratório Editorial Faculdade de Ciências e Letras, 2019)
Developmentalism in Brazil, as object of study, is commonly examined from the post-Vargas rise in the 1930s. This article, however, seeks to examine the foundations underlying Vargas's developmentalist project, based on the subnational experience observed in government of the state of Rio Grande do Sul, as well as of the four currents of ideas that Pedro Cezar Dutra Fonseca conceives, when associated and concatenated, like matrices of the developmentalism in Brazil.